Pelatihan dan Pendampingan Digital Marketing Guna Peningkatan Layanan Penjualan bagi IKM Warung Makan Bude Abimanyu - safaria, siti; Wahyuni, Sri; Yulfanis, Andyni (Institut Keuangan-Perbankan Dan Informatika Asia Perbanas, 2025)
Warung makan sayur mateng was a form of Micro, Small, and Medium Enterprises (MSMEs) that play a vital role in urban community life, including in Bekasi. Their presence not only serves as a provider of affordable meals ready to eat, but also represents an important part of the local social, economic, and cultural dynamics. As an industrial city with high population mobility, Bekasi requires practical solutions for workers, students, and migrants who do not have time to cook. Warung Bude Abimanyu in Mustika Jaya District, address this need by offering a variety of traditional Indonesian dishes while preserving culinary heritage. Economically, these businesses create job opportunities, empower local suppliers, and strengthen the economic circulation of the surrounding community. Challenges MSMEs in the culinary sector are such as limited capital and management capacity, they can be overcome through training support, digital innovation, and community collaboration. Therefore, Warung Bude Abimanyu was not only a solution to the daily food needs of urban society but also serve as a driving force for sustainable people’s economy in Bekasi.